Pengaruh Return on Asset dan Current Ratio terhadap Net Profit Margin PT Adi Sarana Armada Tbk: The Effect of Return on Asset and Current Ratio on the Net Profit Margin of PT Adi Sarana Armada Tbk - Aidan Wira Putra; Bilal Akbar; Fiqri Arifin; Nakhorul Rif'an; Fachri Arkan Alawie (PT Cakrawarti Empat Proksi, 2026)
Business competition in the transportation and logistics sectors requires companies to improve the efficiency of financial performance in order to maintain profitability. This study aims to analyze and empirically test the influence of ROA (X1) and CR (X2) on NPM (Y) in PT Adi Sarana Tbk for the 2018-2025 period. This study uses a quantitative approach with a causal associative method. The data used is secondary data in the form of quarterly financial statements obtained through the official website of the Indonesia Stock Exchange (IDX) and the company's official website. The sampling technique was carried out by the purposive sampling method, which resulted in 32 quarterly data observations that met the research criteria. The data analysis technique used classical assumption tests and multiple linear regression with the help of SPSS software version 27. The results showed that partially, the variable ROA (X1) had a positive and significant influence on NPM (Y) with a significance value of < 0,001. In contrast, the CR variable (X2) was partially shown to have no significant influence on NPM (Y) with a significance value of 0.780. However, simultaneously the variables ROA (X1) and CR (X2) had a significant effect on NPM (Y) with a contribution of 38.7% of the determination coefficient value (R Square). The results of this research can be considered by management in determining asset management strategies to increase the profitability of transportation and logistics service companies.